The role of eWOM in functional foods purchase intention / Chintra Dewi Bajat …[et al.] - Bajat, Chintra Dewi; Ling, Pick-Soon; Mohmed@Wasli, Siti Marhamah; Yong Ming Lee, Kelvin (2023)
The demand for functional foods has also increased with increased health awareness, especially in the post-pandemic era. Consumers tend to seek relevant information in assisting their purchase decision-making. Electronic word-of-mouth (eWOM) is perceived as an innovative source of information as extensive information can be obtained from electronic platforms such as social media. However, the role of the eWOM on functional foods purchase intention (PI) is still undiscovered. Therefore, the study's main objective is to investigate the role of eWOM on functional food PI through an extended theory of planned behaviour (TPB) model. A total of 223 valid responses were gathered in this study and analysed using partial least square structural equation modelling (PLS-SEM). The finding first revealed that attitude (ATT), subjective norm (SN), health consciousness (HC), and eWOM significantly influence functional foods PI. Besides, eWOM also significantly affects ATT, SN, perceived behavioural control (PBC), and HC. In addition, the findings also found that eWOM indirectly significantly influences functional food PI through ATT and SN. This study successfully verified the crucial role of eWOM on functional foods PI, which is theoretically essential as it provides evidence of the role of eWOM on PI. Besides, the practical implications derived from the study's findings are also discussed in this study.